Identification of Phosphorylation Sites within the Herpes Simplex Virus Tegument Protein VP22 - Elliott, Gillian (American Society for Microbiology, 1999)
The herpes simplex virus protein VP22 is a major phosphoprotein of infected cells. In this study, we identify two serine phosphorylation sites within VP22 and show that the N-terminal site is a substrate for casein kinase II, while the extreme C-terminal site is a substrate for another, as yet unidentified, cellular kinase. Furthermore, we show that a mutant of VP22 which has both sites altered is unable to incorporate phosphate in vivo, confirming that there are no other phosphorylation sites within VP22.